(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In a social setting this research can help to understand and guess the feelings and emotions of a person under a variety of circumstances. This information can therefore be used to manage relationships between parents and children, partners, family members, friends, relatives working in local relationships and social interactions. Here both the H-H and HM communication pattern of our system will be very helpful. It will work well for detecting and identifying criminals. Such an investigation will be of great benefit to the community and the nation. This study will be a one-step development in the field of robotics science development. Currently the robots are configured with the MM interface but this study will also help with the MH interface. If a robot can capture the emotions of a person then it can act as a person with emotions. This will be a major development in the field of robotic development and excellent services in the scientific world as a whole.